Investigation of turbine interactions in a tidal device - Blanco, Jesus Maria (Cranfield University, 2009)
Different tidal power generating systems have been studied for a long time. DeltaStream, which has been under development by Tidal Energy Limited has as a salient feature the fact that it is a tubular structure, equilateral triangle shaped and equipped with three horizontal axis turbines placed in each one of the vertices, fitted to nacelles that swivel as the tide flow reverses direction such as to present the rotor disc foremost to the incoming flow. The main objective of this research is to evaluate the degree of angular mismatch that may occur between the turbines of this device as the nacelles are yawed onto a range of angular settings. The desired outcome is the maximisation of the power extractable by the whole system. In order to accomplish this, a numerical approach was carried out so a Computational Fluid Dynamics code FLUENT® v. 6.3 has been used. The numerical model provides a faithful description of the support structure but initially, porous media discs are employed in order to represent the action of the turbine blades. A pressure loss is imposed, according to available data in order to obtain the wake created with the tidal stream. This basic model, considered adequate for an initial sizing of the problem, has been superseded by a realistic description of the blades. In a first stage, a frozen rotor scheme has been considered followed by the most realistic simulations counting the rotation of these blades. Results were finally compared with the previous ones and validated through an experimental prototype. Due to the special character of the matter, which may lead indeed to innovative facts in the future, an extension of the subject would lead to improve results through grid adaptation (using velocity and/or pressure criteria) for all the models, but also with the study of the interferences when considering a further settling of a Delta farm.